The 2018/19 Ebola epidemic the Democratic Republic of the Congo (DRC): epidemiology, outbreak control, and conflict. Issue 1 (March 2020) - Shears, Paul; Garavan, Carrie
Summary: The Democratic Republic of Congo (DRC) (formerly Zaire) was the location of the first Ebola outbreak, in 1976, and since then there have been a total of ten outbreaks in different parts of the country. The current outbreak, the first in eastern DRC (North Kivu and Ituri provinces), began in July 2018, and by December 2019, there had been 3262 cases and 2232 deaths. Within weeks of the first reported cases, the World Health Organisation (WHO) and the DRC Ministry of Health (MOH) initiated a major response programme, with laboratory support, international agencies providing personnel, and material resources. Unlike previous Ebola outbreaks, including the west Africa epidemic, a proven vaccine, and trial therapeutic agents have been available as part of the outbreak response. Two therapeutic agents, mAb114 and REGN-EB3, both monoclonal antibody derived, have shown case fatality rates (CFR) of around 30%, compared to the overall of 66%. Despite these positive interventions, the outbreak has continued for eighteen months. Underlying the outbreak response has been a high number of violent incidents by local militias, and community mistrust and lack of involvement that has hampered many aspects of the response programme. As a result, many cases are not reported early and not transferred to treatment centres, deaths and increased transmission occur in the community, and the response programme is reaching only a proportion of the cases. New strategies to improve community participation, and integrate the Ebola response into the existing health structure are planned to improve the programme effectiveness.